Trade‐off between defense priming by herbivore‐induced plant volatiles and constitutive defense in tomato. Issue 5 (8th January 2020) - Zhang, Peng‐Jun; Zhao, Chan; Ye, Zi‐Hong; Yu, Xiao‐Ping
Abstract: BACKGROUND: Herbivore‐induced plant volatiles (HIPVs) can prime plant defenses and enhance herbivore resistance in neighboring plants. Although a trade‐off between constitutive defense and HIPV emission has been documented in many plant species, little is known about the effect of HIPV variation on defense priming, and whether there is a trade‐off between defense priming and constitutive defense in neighboring plants. RESULTS: Using three tomato genotypes, including two wild types [Moneymaker (MM) and Castlemart (CM)] and one jasmonic acid (JA) overexpression 35S::prosys genotype, we investigated the effects of exposure to volatiles from plants infested by beet armyworm ( Spodoptera exigua ) caterpillars on the defenses and resistance of conspecific neighboring plants. We also analyzed the HIPV emissions from the three genotypes and their constitutive defense and resistance. Exposure to volatiles from S. exigua ‐infested MM plants primed an array of defensive responses (including the accumulation of JA and PI‐II protein and the expression of the defense genes PI‐I and PI‐II ), and enhanced plant resistance against the caterpillars. In contrast, exposure to volatiles from S. exigua ‐infested CM or 35S::prosys did not result in defense priming or an increase in plant resistance. Analyses of HIPVs and gene expression indicated that defense priming in MM was due to enhanced emission of β‐ ocimene and linalool. We further demonstrated that levels of constitutive defense and resistance are low in MM and high in CM and 35S::prosys, suggesting a negative correlation between defense priming and constitutive defense. CONCLUSION: Our findings suggest that there is a trade‐off between defense priming by HIPVs and constitutive defense in tomato. This suggests that defense priming should be used with caution in agriculture. © 2020 Society of Chemical Industry Abstract : This study shows for the first time that there is a trade‐off between defense priming by herbivore‐induced plant volatiles (HIPVs) and constitutive defense in tomato. This result suggests that researchers should pay more attention to using HIPV‐mediated priming for pest control in agriculture.